Preharvest Chitosan Effects on Growth, Yield and Quality of Super Hot and Num Khao Chili Pepper (Capsicum annuum L.) - Somsak Kramchote; Patcharaporn Suwor (My University, 2022)
Two chili pepper (Capsicum annuum L.) cultivars 'Super Hot' and 'Num Khao' grown under field conditions in Thailand were sprayed with 0 (distilled water, control), 25, 50, 100, and 200 ppm chitosan after one week from transplanting and weekly thereafter for five weeks. Chitosan spray improved vegetative growth of both cultivars as measured by increased canopy size. It also increased the plant height of the 'Super Hot' cultivar and reduced leaf curl incidence in the 'Num Khao' cultivar. Leaf size and chlorophyll content were not significantly affected. Fruit were harvested from cultivars at the commercial maturity stage; that is, the red-ripe stage for 'Super Hot' and light green stage for 'Num Khao'. From the four harvests at weekly intervals, chitosan treatment increased the 'Super Hot' yield because of greater fruit production and increased fruit size and there was a higher number of fruit per plant produced by the 'Num Khao' cultivar. Fruit color (L*, a*, b*, and sensory color) was not affected, but overall acceptability increased in response to chitosan spray due to improved size and quality of the 'Super Hot' cultivar and improved appearance, size and glossiness of the 'Num Khao' cultivar. Chitosan at 50 ppm appeared to be the optimum concentration to induce the above effects in both cultivars.
Keywords: Transplanting; Preharvest; Nanocomposite Films for Food Packaging